Verhaltensweisen von Rindern - 1. Auf der Weide - Sommer, Thomas (IWF (Göttingen), 1990)
Auslaß der Milchkühe im Frühjahr. Unbeeinträchtigtes Verhalten auf weitem Raum und trittsicherem Weideboden (vgl. Anbinde- und Laufstallhaltung): Weiden, Fressen, Abliegen, Ruhen, Aufstehen, Rangordnungsverhalten, Kämpfen, Komfortverhalten, soziale Interaktionen. Paarungsverhalten in einer Mutterkuhherde.

Cows put out to pasture of the first fime after winter; locomotion and comfort-seeking behaviour on secure footing; feeding in a group, feeding behaviour of individuals; various social interactions; laying down, lying, and standing up. A bull checks cows in breeding herd for estrus; pursuing a cow and increasing approaches; copulation attempts; successful copulation.
Keywords: Life Sciences; Rangordnung / Artiodactyla; Kampfverhalten / Mammalia; Paarung / Artiodactyla; Hinlegen / Artiodactyla; Aufstehen / Artiodactyla; Nahrungsaufnahme / Artiodactyla; Herde / Artiodactyla; Komfortverhalten / Artiodactyla; Rind; Bos taurus; pecking order / Artiodactyla; fighting behaviour / Mammalia; copulation / Artiodactyla; laying down / Artiodactyla; standing up / Artiodactyla; ingestion / Artiodactyla; herd; comforting behaviour / Artiodactyla; cow; cattle; Bos taurus